MOISTURE CONDITIONS PATTERNS IN ROAD EMBANKMENT CLAY SOILS DEPTH - Vynnykov, Yu. L.; Lvovska, T. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article deals with optimal compaction criteria of road embankment soils improving, which provide their long-term strength. Physical experiment methodology for patterns establishment of water migration in subgrade embankment depth, in the capacity factors of what it is accepted: clay soil type (its number plasticity); moisture, at what the soil was compacted; soil skeleton density; embankment height; «rest» time after subgrade erection and before it’s operation are developed and realized. By laboratory and field tests water migration patterns in compacted subgrade soils depth are established. As a result of statistical processing of laboratory and field research results, the empirical dependence of compacted clay soil stabilized moisture for their multilayer consolidation in relation to soil skeleton density and plasticity number values is obtained.